2010
DOI: 10.1111/j.1524-4725.2010.01531.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Regression in Merkel Cell Carcinoma

Abstract: The authors have indicated no significant interest with commercial supporters.M erkel cell carcinoma (MCC) is a malignant neuroendocrine tumor that typically affects elderly patients. 1 It is aggressive, with frequent recurrences after excision. Regional and distant metastases develop in approximately 40% of cases. Patients without lymph node involvement have been reported to have a survival rate of 75% at 5 years, whereas patients with distant metastases have a survival rate of 25% at 5 years. 2 The etiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…To the best of our knowledge, dermoscopic studies of MCC have been reported for only 2 cases of spontaneously regressive MCC [8]. In both cases a polymorphous aspect of the vascular pattern was observed: linear irregular and regular vessels in one case and linear irregular vessels associated with a homogenous milky-red background in the second case.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To the best of our knowledge, dermoscopic studies of MCC have been reported for only 2 cases of spontaneously regressive MCC [8]. In both cases a polymorphous aspect of the vascular pattern was observed: linear irregular and regular vessels in one case and linear irregular vessels associated with a homogenous milky-red background in the second case.…”
Section: Discussionmentioning
confidence: 97%
“…Due to its red, pink or purple nodular presentation, the differential diagnosis includes cutaneous lymphoma, atypical fibroxanthoma, porocarcinoma, achromic melanoma, angiosarcoma, hemangioma or skin metastasis from internal malignancy. The dermoscopic aspect of MCC has been previously reported only in two case reports of spontaneous regressive MCC [8]. The aim of this study was to define the main dermoscopic patterns observed in MCC, to compare them with other known dermoscopic features of amelanotic malignant tumors and to address the question whether those criteria were specific or not.…”
Section: Introductionmentioning
confidence: 99%
“…MCC tumors sometimes regress following improvement in immune function [13, 14] underscoring the importance of immune surveillance in the development of MCC. Additionally, there are several reported cases of complete spontaneous regression in the MCC literature (a far greater number than expected for its rarity) that suggest a sudden recognition by the immune system leading to the clearance of MCC [15-20]. These epidemiologic data raised the possibility of an infectious etiology for MCC.…”
Section: Link With Immune Suppression Leads To Discovery Of Merkel Cementioning
confidence: 99%
“…White zones together with streaks were mentioned in two previously published articles. [67] Milky pink zones, linear irregular vessels and branching vessels were also demonstrated in Merkel cell carcinoma. [67] In case 1, yellowish-white zones were surrounded by crown like shaped branching vessels.…”
Section: Discussionmentioning
confidence: 99%
“…[67] Milky pink zones, linear irregular vessels and branching vessels were also demonstrated in Merkel cell carcinoma. [67] In case 1, yellowish-white zones were surrounded by crown like shaped branching vessels. These findings are also common in sebaceous hyperplasia,[8] and molluscum contagiosum.…”
Section: Discussionmentioning
confidence: 99%